Application of Nanotechnology in Agriculture: Opportunities and Challenges in the Context of Environmental Sustainability - Michelle C. Lallawmkimi; Soumya Patil; D. K. Upadhyay; Niren Majumdar; Abinaya B.; G.Sadaya Kumar; Chandan Kumar Panigrahi (Archives of Current Research International, 2025)
Nanotechnology is an emerging field with immense potential to revolutionize agriculture by enhancing productivity, resource efficiency, and sustainability. Its applications span diverse areas, including nano-fertilizers for improved nutrient uptake, nano-pesticides for targeted pest control, and nanosensors for real-time monitoring of soil and crop health. These advancements address critical agricultural challenges, such as nutrient inefficiency, pest resistance, and environmental degradation. Nano-enabled smart delivery systems optimize the use of fertilizers and pesticides, reducing environmental contamination and improving yield. Nanotechnology also facilitates soil remediation, enhances microbial health, and provides innovative water purification techniques, making it instrumental in mitigating resource scarcity and pollution. Its role in precision agriculture, through IoT-integrated nanosensors, enables data-driven farming practices that improve decision-making and resource allocation. Despite its promise, the adoption of nanotechnology faces barriers, including potential toxicity of nanomaterials, long-term environmental risks, and concerns over food safety and human health. High production costs, limited scalability, and a lack of regulatory frameworks hinder widespread implementation, particularly in developing countries. Future research must focus on eco-friendly and biodegradable nanomaterials, scalable manufacturing methods, and the development of cost-effective technologies accessible to smallholder farmers. Robust policy frameworks, standardized safety guidelines, and public-private collaborations are essential to ensure the safe and ethical integration of nanotechnology in agriculture. Equally important are educational initiatives to enhance farmer awareness and build public trust in these innovations. By addressing these challenges, nanotechnology can play a transformative role in creating a sustainable, climate-resilient agricultural system capable of meeting the demands of a growing global population while protecting environmental and human health.